MDPV in Queensland Drivers. Issue 2 (3rd March 2016) - Griffiths, Andrew; Johnston, Michelle; Hadley, Lenore
Abstract : 3, 4-methylenedioxypyrovalerone (MDPV) is a novel psychoactive drug structurally related to cathinone with powerful CNS stimulant effects. MDPV has a marked potential to impair driving performance, however, only limited data are available on the prevalence and drug concentrations of MDPV in driver specimens. In this study, data relating to MDPV positive driver specimens in Queensland were examined. MDPV first appeared in Queensland illicit drug seizures in 2010 and subsequently began to appear in driver specimens in 2011. Between 2011 and 2013 the drug was identified in 33 blood specimens collected from drivers who either had been injured during a motor vehicle accident, or were suspected of non-alcohol related drug impairment by investigating police or forensic medical officers. Examination of the driver data revealed a large proportion of the MDPV positive specimens had originated from the sparsely populated Mount Isa region in the northwest of Queensland. MDPV concentrations were within a range of <0.01 to 0.30 mg/kg, (median 0.05 mg/kg) and indications of suspected drug impairment were noted by investigating police in >50% of cases. Seventy percent of MDPV positive drivers were male, 30% female and the median age was 33 years.